Evaluation of Public Policy Implementation in Natural Resource Management: A Case Study in Makassar City - Muhammad Natsir Mallawi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research evaluates the implementation of public policies related to natural resource management in Makassar City, Indonesia. Using a qualitative case study approach, this study examines the effectiveness, challenges, and impacts of these policies on sustainable development practices. Data was collected through in-depth interviews with 25 key informants including government officials, resource managers, and affected community members, complemented by document analysis of policy papers and reports. The findings reveal significant gaps between policy formulation and implementation due to institutional fragmentation, limited community participation, and inadequate human resource capacity. While some policies have increased public awareness of conservation, others have failed to prevent environmental degradation, including water quality deterioration and deforestation. This study contributes to understanding the complex dynamics of natural resource governance in rapidly developing urban centers and offers practical recommendations for improving policy implementation through enhanced inter-agency coordination, meaningful community engagement, and capacity building initiatives.